Exploration of the renoprotective effect of Yi-Shen-Hua-Shi granules on db/db mice and the mechanism of podocyte apoptosis based on the GRP78/CHOP signaling pathway - Cai, Yanmo; Liu, Yunhua; Wang, Sitong; Jin, Ge; Zhou, Kaidong; Zhou, Xin; Zhang, Xinxue; Zhang, Min; Zhao, Zongjiang (Frontiers in Pharmacology, 2025)
ObjectiveYi-Shen-Hua-Shi (YSHS) granules are a widely utilized Chinese medicine formula for treating diabetic kidney disease (DKD). Although their effectiveness in treating DKD is established, the precise regulatory mechanism remains unclear. We aimed to explore the potential targets and mechanisms of action of YSHS in delaying DKD progression through network pharmacology and experimental validation.MethodsNetwork pharmacology was employed to identify the potential targets and signaling pathways of YSHS in treating DKD, which was hypothesized to be associated with endoplasmic reticulum stress and apoptosis, and these predictions were validated through animal and cellular experiments. Following a 12-week YSHS intervention in db/db mice, assessments were conducted on blood glucose, lipid levels, renal function indices (24-h urinary protein, blood glucose, serum creatinine, blood urea, and urinary albumin-to-creatinine ratio), and kidney pathology. Apoptosis in mouse podocyte clone-5 (MPC-5) cells was assessed using TUNEL labeling. The expression levels of GRP78, PERK, p-PERK, CHOP, Bcl-2, Bax, and Nephrin proteins and mRNAs in mouse kidney tissues and MPC-5 cells were evaluated by immunohistochemistry, Western blotting, and real-time PCR.ResultsYSHS significantly improved the general status of db/db mice, with a significant reduction in body mass, renal function indices, total cholesterol, triglycerides, and low-density lipoprotein. Pathological staining showed reduced renal tissue damage in mice, and electron microscopy revealed reduced pedunculopontine fusion and basement membrane thickening. YSHS decreased GRP78, PERK, p-PERK, CHOP, and Bax proteins and mRNA levels in renal tissues and MPC-5 cells (p < 0.05 and p < 0.01) while increasing the expression level of Nephrin protein and Bcl-2 mRNA (p < 0.05 and p < 0.01).ConclusionYSHS inhibited podocyte apoptosis, protected the glomerular filtration barrier, attenuated proteinuria, and improved renal function indices by activating the GRP78/CHOP signaling pathway in the kidneys and the in vitro cultured podocytes of db/db mice.